2020
DOI: 10.1002/adfm.202001692
|View full text |Cite
|
Sign up to set email alerts
|

Low‐Dimensional Contact Layers for Enhanced Perovskite Photodiodes

Abstract: Controlling defects and energy‐band alignments are of paramount importance to the development of high‐performance perovskite‐based photodiodes. Yet, concurrent improvements in interfacial contacts and defect reduction simply by tailoring bottom contacts have not been investigated. An effective strategy is reported that can simultaneously improve energy‐band alignments and structural defects by introducing low‐dimensional contact (LDC) layers at the bottom interface. It is found that LDC‐based perovskites consi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 38 publications
1
28
0
Order By: Relevance
“…[17,116] When the resultant strain belongs to tensile strain, the non-radiative recombination losses, and the subsequent decrease of device performance could be accelerated. [30] Our recent work has demonstrated that inserting a bottom buffer layer can mediate the lattice strain of perovskite films whilst modulating structural defects and crystallization, [117] resulting in improved band alignment. To be more specific, by inserting a pre-coating layer of large organic molecules before the perovskite deposition, low-dimensional contacts would be formed at the bottom side of final perovskite films (Figure 7a).…”
Section: Surface Buffer Materials For Growing Better Perovskitesmentioning
confidence: 99%
“…[17,116] When the resultant strain belongs to tensile strain, the non-radiative recombination losses, and the subsequent decrease of device performance could be accelerated. [30] Our recent work has demonstrated that inserting a bottom buffer layer can mediate the lattice strain of perovskite films whilst modulating structural defects and crystallization, [117] resulting in improved band alignment. To be more specific, by inserting a pre-coating layer of large organic molecules before the perovskite deposition, low-dimensional contacts would be formed at the bottom side of final perovskite films (Figure 7a).…”
Section: Surface Buffer Materials For Growing Better Perovskitesmentioning
confidence: 99%
“…Over the last decade, perovskite photovoltaics (PPV) have shown dramatic achievements in both the device efficiency and long-term stability 1 7 . Despite notable advances in the device performance, there is still a certain gap between the record power conversion efficiencies (PCEs) and the theoretical limit defined by the Shockley-Queisser theory.…”
Section: Introductionmentioning
confidence: 99%
“…However, even in photodiode devices with charge transport materials to suppress carrier injection form the electrode, most polycrystalline perovskite detectors still suffer from unacceptably large dark current. It was highlighted that the undesired interfacial energy barrier that incapable of completely blocking carrier injection at high electrical field is known as a main reason for the large dark current 109 . Meanwhile, thermally activated carrier injection via the defect states within the bandgap could also lead to a large dark current in a photodiode type detector 64 .…”
Section: Discussionmentioning
confidence: 99%
“…main reason for the large dark current. 109 Meanwhile, thermally activated carrier injection via the defect states within the bandgap could also lead to a large dark current in a photodiode type detector. 64 Nonetheless, the origin of the high dark current remains to be an open question, which require further investigations.…”
Section: T a B L E 3 Key Parameters Of Polycrystalline Perovskites Bamentioning
confidence: 99%